Difel - Family vs business in a family business - Siqueira, Manuel Maria Fezas Vital de (2018)
This case study is based on Difel, a small book publisher and family business. In a time of deep financial complications, family conflicts and unaligned views regarding the company’s path are jeopardizing its continuation. This case is intended to demonstrate that decision-making and direction setting can be hard tasks in family businesses, as well as the impact of socioemotional wealth and the importance of procedural justice. The teaching note provides guidance in order to accurately present this case in a classroom. It incorporates several discussion questions and its respective answers, which connect the case to relevant family business content and theory.